THE ROLE OF BUMDES IN IMPROVING WELFARE IN TOLONDADU II VILLAGE, BOLAANG UKI SUB-DISTRICT BOLAANG MONGONDOW SELATAN DISTRICT - rina tontoli; Aryati Hamzah; Siskawati Yahya (LP2M Universitas Bina Mandiri Gorontalo, 2022)
The purpose of compiling the final project report is to find out the role of BUMDes Minanga Jaya in improving welfare in Tolondadu II Village, Bolaang Uki District, South Bolaang Mongondow Regency. Data obtained through observation, interviews and comments using descriptive methods. There were 3 informants in writing this final report, namely Ms. Aisa Gobel, Mr. Risno Masaguni and Mr. Abubakar Tuadingo. Report on the Final Results of Writing the Role of BUMDes as a Motivator in Tolondadu II Village, Bolaang Mongondow Selatan Regency, as the spearhead and pioneer of Business Entities.